2020
DOI: 10.1016/j.jaim.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Reinventing nano drug delivery systems for hydrophilic active ingredients in Ayurvedic lipid based formulations containing poly herbal decoction

Abstract: Background Anu Tailam, an Ayurvedic medicated oil where ‘anu’ meant for atom and ‘tailam’ meant for oil and virtually meant for ‘oil of subtle or atomic size particles’. Since the major active ingredients in this formulation are incorporated from the polyherbal decoction, it is expected to contain predominantly water soluble ingredients. Objectives It is hypothesized that these polar active botanical ingredients are present in the formulation should be either suspended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Various pharmacological agents, including intra-nasal delivery of TLR2/6 agonist, are studied to prevent the entry of viruses and control the infection ( 24 , 53 55 ). Ayurveda-based Anu Taila (Oil) derived from several important medicinal plants nourishes all the sensory organs, including nose, and helps in relieving congestion in the nostrils, chronic sinusitis ( 20 , 21 ), and controlling the pro-inflammatory cytokines ( 56 ). Various authors showed a reduced viral load in the lungs after the prophylactic nasal instillation of Anu Taila ( 21 , 22 , 24 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various pharmacological agents, including intra-nasal delivery of TLR2/6 agonist, are studied to prevent the entry of viruses and control the infection ( 24 , 53 55 ). Ayurveda-based Anu Taila (Oil) derived from several important medicinal plants nourishes all the sensory organs, including nose, and helps in relieving congestion in the nostrils, chronic sinusitis ( 20 , 21 ), and controlling the pro-inflammatory cytokines ( 56 ). Various authors showed a reduced viral load in the lungs after the prophylactic nasal instillation of Anu Taila ( 21 , 22 , 24 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sanshamani Vati ( Tinospora cordifolia ), commonly named as Guduchi, boosts immunity and acts as an immune modulator ( 19 ). Anu Taila (Oil) nourishes all the sensory organs and helps in relieving congestion in the nostrils, chronic sinusitis ( 20 , 21 ). The rationale behind utilization of the above drugs was as follows: all the formulations and their suggested doses have been used in Ayurveda since ages with well-documented safety aspects and no visible side-effects ( 22 ); all of them were recommended by the Ministry of AYUSH, Government of India, for the prevention of health and boosting immunity for COVID-19 prophylaxis ( 15 ); the efficiency of all three drugs and their active ingredients were proved by the evidence of the published literature and reported with anti-viral/reduced viral load and immunomodulatory activity ( 21 , 23 , 24 ), none of them had any toxic effect at the prescribed application dose ( 22 ); all of them were cost-effective; easy to use; manufactured in reputed Government approved manufacturing unit.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a classical ayurvedic medicine, Anu tailya was used by Maharishi Charak more than 5,000 years ago for therapeutic purposes. (Duraipandi and Selvakumar, 2020; see the enclosed supplement information). Here, we report that intranasal instillation of both til tailya and Anu oil limited the viral entry and replication in the lungs associated with SARS-CoV2 infection in hamsters.…”
Section: Introductionmentioning
confidence: 99%
“…Since pharmaceutical drugs may have many off-target effects, therapeutics based on herbal extracts have recently gained much attention ( Matveeva et al, 2020 ; De Pellegrin et al, 2021 ; Jan et al, 2021 ; Li et al, 2021 ). Here, we evaluated the efficacy of two ayurvedic intranasal (herbal) oil formulations, Anu oil and til tailya ( Duraipandi and Selvakumar, 2020 ), in hamster SARS-CoV2 challenge model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation